2012
DOI: 10.5338/kjea.2012.31.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Current research trends for heavy metals of agricultural soils and crop uptake in Korea

Abstract: BACKGROUND: Increase of heavy metals in agricultural ecosystem has become a social issue nationwide as it is related to public health. This review was performed to find out more systematic and integrated future researches on heavy metals using up to date articles published in the Korean journals related to agricultural environment. METHODS AND RESULTS:Researches on heavy metals in agricultural soils and plant uptake were categorized by the establishment of criteria, analytical methods, monitoring, management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
3
0
7
Order By: Relevance
“…에 대한 인체 노출의 주요인이 되며, 축적된 중금속은 만성적 인 위해성을 나타낸다 (Nan et al, 2002;Cui et al, 2004;Lee et al, 2012). 토양에서 농산물로의 중금속 전이계수는 식물체의 중금속 축적과 더불어 농산물의 안전성에 직접적인 영향을 미치는 주요인자로 이용될 것이라는 보고가 있다 (Greger et al, 2007;Uchida et al, 2007;Dudka et al, 1996;Puschenreiter and Horak, 2000;Nan et al, 2010).…”
unclassified
See 1 more Smart Citation
“…에 대한 인체 노출의 주요인이 되며, 축적된 중금속은 만성적 인 위해성을 나타낸다 (Nan et al, 2002;Cui et al, 2004;Lee et al, 2012). 토양에서 농산물로의 중금속 전이계수는 식물체의 중금속 축적과 더불어 농산물의 안전성에 직접적인 영향을 미치는 주요인자로 이용될 것이라는 보고가 있다 (Greger et al, 2007;Uchida et al, 2007;Dudka et al, 1996;Puschenreiter and Horak, 2000;Nan et al, 2010).…”
unclassified
“…전이계수는 농산물의 중금속 생물학적 이용도의 차이 를 확인하는데 이용되며, 실제적으로 토양에서 중금속 이동의 측정 지표로 사용된다. Lee(2012) 등은 토양 내 중금속이 농산물로 흡수되는 정 도는 토양의 특성에 따라 다르지만 작물의 중금속 흡수에 가 장 큰 영향을 미치는 인자는 토양 중 중금속 함량이며, 토양 중 중금속 함량이 증가함으로써 작물 내 중금속 함량이 증가 함을 확인하였다. 토양에서 농산물로의 중금속의 전이계수는 토양 특성, 식물체 부위, 그리고 농산물 종류에 따라 다양하 며, 카드뮴과 아연은 1∼10, 구리와 납은 0.01∼0.1로 산출되 었다 (Klocke et al, 1984).…”
unclassified
“…It appeared that 0.01 M Ca(NO3)2 extraction was a better option for the determination of bioavailable metal(loid)s in soils. Lee et al (2012) reported various patterns of crop uptake and transformation of heavy metal(loid)s with different crop species, varieties, parts, growing seasons, plowing, and irrigation methods. Table 6 showed the regression equations …”
Section: Arsenic Contents In Soils Using Single Extraction Methodsmentioning
confidence: 99%
“…카드뮴에 의해 유도되는 활성산소종의 소거에 항산화효소 및 비효소적인 GSH의 역할과 기능은 여러 연구를 통하여 잘 구명되었지만 (Harada et al, 2002;Meuwly and Rauser, 1992), 산화적인 스트레스에 의해 야기된 활성산 소종 소거, 산화 ․ 환원 (redox) 조절, 세포주기, 세포성장 및 손상된 DNA 복구 등에 관여하는 AsA의 기능과 역할은 아직도 연구가 미흡한 상태이다 (Kerk and Feldman, 1995;Luwe, 1996). 카드뮴의 식물전이는 작물의 재배환경과 더불어 여러 이온들의 상호작용에 따라 흡수 및 축적되는 정도가 상이하 게 나타난다 (Fergusson, 1990;Jung et al, 2016;Lee et al, 2012;Park et al, 2009). 비료의 3요소 중의 하나인 인과 중금속인 비소의 길항작용에 관한 연관성 연구는 여러 연구보고들을 통하여 확실한 정설로 자리매김을 하고 있는 실 정임에도 불구하고 (Brachhage et al, 2014;Gomes et al, 2014), 카드뮴과 인의 상호연관성 연구는 일부 식물에서의 연구를 제외하고 아직도 미진한 상태이므로 깊이있는 연구가 필요할 것으로 판단된다 (Arshad et al, 2016).…”
Section: Introductionunclassified